FORMATION OF THE COMMUNICATIVE COMPETENCE TO TECHNICAL UNIVERSITY STUDENTS IN THE LIGHT OF UNIVERSAL COMPETENCES - Kalyanova, Ludmila (Revista Inclusiones, 2019)
The article deals with the formation of the communicative competence to technical university students in the light of universal competences. Taking into consideration the fact that nowadays it is necessary to act in the conditions of the competence approach, continuity of education and technologization of the educational process. All attention in this situation is maximally directed to the professional side of training and acquisition of professional competences by students. Along with the formation of professional competences, due attention is paid to the formation of general cultural and communicative competences, without which a graduate of a technical university will not be formed as a specialist of a high professional level. The student must quickly analyze the incoming information, creatively solve the problems created in the conditions of uncertainty, and must also have a communicative competence. In light of the new requirements of modern education, the formation of the universal competences is given priority, due attention is paid to the formation of the communicative competence since a high-level specialist is required to possess communication skills, both in the state language of the Russian Federation and in a foreign language.